Malinowsky for today? - Damon, Frederick H (2022)
From the point of view of a contemporary Kula Ring ethnographer, this paper surveys Malinowski’s heritage, sums up the current state of Kula Ring research, and asks of the status of the ethnographic research heritage Malinowski did much to define. All recent Kula Ring anthropologists partly define themselves with respect to Malinowski’s tradition. And the results of their work over the last 50 years again made the region central to the discipline for part of the recent past. But today Malinowski’s Trobriand corpus is being redefined. New lines of inquiry are contributing to our understanding of the area. And Malinowski’s methods have fertilized other portions of our social system and branches for self-reflection. As it should be, what Malinowski helped define is very much with us.